Focussed assessment of certain existing MRLs of concern for acetamiprid and modification of the existing MRLs for table olives, olives for oil production, barley and oats. (16th May 2018) - ; Brancato, Alba; Brocca, Daniela; Carrasco Cabrera, Luis; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; et al.
Abstract: In compliance with Article 43 of Regulation (EC) No 396/2005, EFSA received from the European Commission a mandate to provide its reasoned opinion on the existing maximum residue levels (MRLs) for acetamiprid which might lead to consumers intake concerns on the basis of the new toxicological reference values agreed upon by Member States (MSs) in October 2017. In order to identify the MRLs of potential concern that require a more detailed assessment, EFSA performed a preliminary risk assessment, identifying a risk for consumers for 12 commodities. Measures for reduction of the consumer exposure were assessed by EFSA and should be considered by risk managers. Furthermore, in accordance with Article 6 of Regulation (EC) No 396/2005, ADAMA Makhteshim Ltd submitted two requests to modify the existing MRL for acetamiprid in table olives, olives for oil production, barley and oats. The data submitted in support of the requests were found to be sufficient to derive MRL proposals for all crops under assessment. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of acetamiprid according to the intended agricultural practices on table olives, olives for oil production, barley and oats is unlikely to present a risk to consumer health.